Adverse childhood experiences and emotion dynamics in daily life: a two sample study* - Peltonen, Kirsi; Tammilehto, Jaakko; Flykt, Marjo; Vänskä, Mervi; Kuppens, Peter; Bosmans, Guy; Lindblom, Jallu (Informa UK Limited, 2025)
Research suggests that adverse childhood experiences (ACEs) can have life-long consequences on emotional functioning. However, it is unclear how ACEs shape the dynamic features of everyday emotions. In the current preregistered study with two adult ecological momentary assessment samples (Ns = 122 and 121), we examined the linear and curvilinear associations of ACEs with daily emotion dynamic features. We expected ACEs to show linear associations with a higher baseline level, variability, and inertia of negative emotions, as well as a lower baseline level of positive emotions. Moreover, we expected ACEs to show U-shaped curvilinear associations with the variability of negative and positive emotions. The results did not support our hypotheses. Instead, ACEs showed an inverted U-shaped association with the baseline level and variability of negative emotions. Furthermore, ACEs also showed a U-shaped association with the baseline level of positive emotions and a linear association with higher variability of positive emotions. However, all associations were present in only one of the two samples. Our study underscores the critical need to incorporate a broad spectrum of ACEs in research samples to adequately capture their developmental consequences and the role of ACEs in contributing to the baseline level and variability of daily emotions.